2021
DOI: 10.3389/fnint.2021.647928
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Idiopathic Sensory Processing Disorder in Young Children

Abstract: This study described the developmental and behavioral characteristics of children identified with idiopathic sensory processing disorder (SPD) as well as the relations among specific types of SPD as proposed by the nosology presented by Miller et al. (2007), adaptive behavior profiles, and behaviors associated with mental functioning. A retrospective, non-experimental design applying descriptive and correlational analyses was used. Data were obtained from clinic medical records of 78 children ages 2 to 7 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 44 publications
0
9
0
1
Order By: Relevance
“…Unlike the comparison group, the ASD children appeared more likely to have abnormalities across multiple sensory domains, whereas most of the comparison group children had weaker abnormal sensory features. Already, Leekam et al [35] has indicated that sensory abnormalities are more prevalent in children with autism than in children with other developmental disabilities, independently from the cognition level, and, as suggested by Mulligan and collaborators [7], adaptive behaviour across functional domains may be impacted by the severity of sensory processing deficits of the children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike the comparison group, the ASD children appeared more likely to have abnormalities across multiple sensory domains, whereas most of the comparison group children had weaker abnormal sensory features. Already, Leekam et al [35] has indicated that sensory abnormalities are more prevalent in children with autism than in children with other developmental disabilities, independently from the cognition level, and, as suggested by Mulligan and collaborators [7], adaptive behaviour across functional domains may be impacted by the severity of sensory processing deficits of the children.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, SPD can impact self-regulation, influencing behaviour, daily-life activities, learning and neuropsychomotor development [1,5,6]. Recently, Mulligan [7] suggested that adaptive behaviour can be frequently altered by sensory processing impairment during childhood and that the severity of SPD seems to be negatively correlated with adaptive skills.…”
Section: Introductionmentioning
confidence: 99%
“…Sensory processing, or multisensory integration, occurs in specific areas of the brain as sensory input from the external environment is transformed into usable data, supporting our ability to act in the world (Bundy and Lane, 2019). Epidemiological studies estimate that 5-16% of children in the general population experience sensory processing patterns that impact their daily life (Ayres, 1971;Ahn et al, 2004;Dunn et al, 2016;Galiana-Simal et al, 2020;Mulligan et al, 2021). Using Dunn's Sensory Processing Framework (2014), sensory processing patterns can be characterized in four quadrants: (i) low registration, (ii) sensory seeking, (iii) sensory sensitivity, and (iv) sensory avoiding.…”
Section: Introductionmentioning
confidence: 99%
“…The Sensory Integration and Praxis Test (SIPT) is regarded as the "gold standard" test for detecting sensory discrimination and sensorimotor abnormalities [6]. However, it does not measure sensory modulation [14]. Sensory modulation is typically measured by the Sensory Profile (which has two versions) and the Sensory Processing Measure [6,14].…”
Section: Introductionmentioning
confidence: 99%
“…However, it does not measure sensory modulation [14]. Sensory modulation is typically measured by the Sensory Profile (which has two versions) and the Sensory Processing Measure [6,14].…”
Section: Introductionmentioning
confidence: 99%